FAT score: an Indian insight to a novel diagnostic score to differentiate non-alcoholic steatohepatitis (NASH) from simple steatosis - Jijo Varghese; Anoop K V; Krishnadas Devadas; Tharun Tom (SpringerOpen, 2021)
Abstract Background The aim of this study was to propose a simple predictive score to differentiate NASH from simple steatosis. Results This study included 64 patients who had biopsy-proven NAFLD, of which 34 patients had steatohepatitis and 30 had simple steatosis. Clinical, anthropometric, and biochemical variables of the study population were analyzed. Univariate analysis showed platelet count, ferritin, and transaminases (ALT&AST) were predictors of NASH. This led to the proposal of a new diagnostic tool, FAT score (F signifies Ferritin, A indicates AST&ALT, T denotes t in Platelet) with AUROC of 0.95. The ROC curves for the significant variables were plotted and cutoff values were identified. Each component is awarded a score of 0 or 1, based on this cutoff value. The component is awarded a score of 1 if the component score is above the cutoff value and 0, if the score is below cutoff. The maximum score which can be obtained is 4. A score of ≥ 3 was able to predict NASH from simple steatosis with a sensitivity of 76.5% and a specificity of 100%. The score was validated with a cohort of 84 liver biopsy patients wherein a cutoff ≥ 3 was found to give a specificity of 100% in the validation cohort. Conclusions FAT score is a simple predictive model to differentiate NASH from simple steatosis (cutoff of more than or equal to 3) without performing a liver biopsy. A FAT score less than 3 rules out the need for biopsy.